THE METHOD OF THE WORKING ACCURACY INCREASING WITH THE HELP OF COMBINED LATHE TOOLS - S.V. NEKHOROSHKOV; U.S. DUBROV; G.S. NIKOLAEVA (Advanced Engineering Research)
There are given the research results conformably to the working accuracy with the help of combined carbide-tipped with heightened thermal conductivity lathe tools. The thermal broadening reduction of the newly-designed combined lathe tools is determined.